2002
DOI: 10.1091/mbc.01-06-0314
|View full text |Cite
|
Sign up to set email alerts
|

Phosphoinositides Regulate Membrane-dependent Actin Assembly by Latex Bead Phagosomes

Abstract: Actin assembly on membrane surfaces is an elusive process in which several phosphoinositides (PIPs) have been implicated. We have reconstituted actin assembly using a defined membrane surface, the latex bead phagosome (LBP), and shown that the PI(4,5)P 2 -binding proteins ezrin and/or moesin were essential for this process (Defacque et al., 2000b). Here, we provide several lines of evidence that both preexisting and newly synthesized PI(4,5)P 2 , and probably PI(4)P, are essential for phagosomal actin assembly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
61
0
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(71 citation statements)
references
References 82 publications
(126 reference statements)
9
61
0
1
Order By: Relevance
“…However, in contrast to PI(4)P, PI(4,5)P 2 was not required for PLF, in line with a direct effector function for PI(4)P. This does, of course, not exclude a role of PI(4,5)P 2 in late phagosome maturation in vivo. For example, conversion of PI(4)P to PI(4,5)P 2 on phagosomes is required for polymerization of F-actin (21), which facilitates their fusion with lysosomes (42). This possible in vivo role of PI(4,5)P 2 would not be reconstituted in our cell-free PLF assay, which does not require actin polymerization (2).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…However, in contrast to PI(4)P, PI(4,5)P 2 was not required for PLF, in line with a direct effector function for PI(4)P. This does, of course, not exclude a role of PI(4,5)P 2 in late phagosome maturation in vivo. For example, conversion of PI(4)P to PI(4,5)P 2 on phagosomes is required for polymerization of F-actin (21), which facilitates their fusion with lysosomes (42). This possible in vivo role of PI(4,5)P 2 would not be reconstituted in our cell-free PLF assay, which does not require actin polymerization (2).…”
Section: Discussionmentioning
confidence: 97%
“…Conversely, early subreactions of phagosome maturation (i.e., fusion of early phagosomes with early endosomes or late endosomes) did not require PI(4)P (this study). Both, PI(4)P and PI(4,5)P 2 have occasionally been detected in phagolysosomes (21) and lysosomes (19,20), yet specific functions have only been attributed to PI(4,5)P 2 . Even in other cellular processes, PI(4)P was long thought to be merely the precursor of PI(4,5)P 2 (41) and here, too, phagosomal PI(4)P was converted to PI(4,5)P 2 under fusion conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, flashing does not depend on the molecular features of the internalized object. Inhibition of PI-3 kinase does not block comet tail formation (Rozelle et al, 2000) nor in vitro assembly of actin on bead phagosomes (Defacque et al, 2002). Similarly, inhibition of PI 3-kinase had no effect on flashing.…”
Section: Repeated Cycles Of Actin Assembly and Disassembly Occurs On mentioning
confidence: 96%
“…For example, Hope & Pike, 1996 showed that polyphosphoinositide phosphatase, but not several other phosphoinositide-utilizing enzymes, is highly enriched in a low-density Triton-insoluble membrane fraction that contains caveolin; this fraction is also enriched in polyphosphoinositides, containing approximately one-fifth of the total cellular phosphatidylinositol (4,5)P 2 . Defacque et al, 2002 suggested that PI(4,5)P 2 may exist in raftlike microdomains on latex bead phagosomes after isolation. On activation of cells with agonists or addition of ATP to the in vitro actin assay, PIPs are rapidly synthesized and may aggregate laterally into larger raft domains.…”
Section: Phosphoinositides and Lipid Rafts In Phagocytosismentioning
confidence: 99%